Beyond the Manager’s Moral Dilemma: Rethinking the ‘Ideal Type’ Business Ethics Case - Bridgman, Todd (School of Management Working Papers, 2010)
Case teaching occupies a central place in the history of business education and in recognition of its significance, the Journal of Business Ethics recently created a new section for cases. Typically, business ethics cases are used to teach moral reasoning by exposing students to real life situations which puts them in the position of a decision-maker faced with a moral dilemma. Drawing on a critical management studies‟ critique of mainstream business ethics, this paper argues that this „ideal type‟ decision-focused case underplays the social, political and economic factors which shape managerial decisions. An alternative „dark side‟ case approach is presented, which highlights the structural features of capitalism and the role of government in regulating the market. The „dark side‟ approach is illustrated with the case of a New Zealand woman, dependent on an oxygen machine, who died when her power was disconnected by her State owned electricity supplier because of an unpaid bill. The case considers the actions of both the company and the industry regulator within the context of a „light-handed‟ approach to government regulation. The paper concludes with a discussion of how this approach to the case method, which moves beyond managers and their moral dilemmas, can provide students with a deeper understanding of the complexity of business ethics.